Resection of Mixed Hepatocellular‐Cholangiocarcinoma, Hepatocellular Carcinoma, and Intrahepatic Cholangiocarcinoma. Issue 7 (2nd July 2020) - Holzner, Matthew L.; Tabrizian, Parissa; Parvin‐Nejad, Fatemeh P.; Fei, Kezhen; Gunasekaran, Ganesh; Rocha, Chiara; Facciuto, Marcelo E.; Florman, Sander; Schwartz, Myron E.
Abstract : Mixed hepatocellular‐cholangiocarcinoma (HCC‐CC) is a biphenotypic liver cancer thought to have unfavorable tumor biology and a poor prognosis. Surgical outcomes of HCC‐CC remain unclear. We aimed to evaluate the clinical characteristics and surgical outcomes of HCC‐CC. We analyzed a series of patients undergoing resection for HCC‐CC (n = 47), hepatocellular carcinoma (HCC; n = 468), and intrahepatic cholangiocarcinoma (ICC; n = 108) at a single Western center between 2001 and 2015. Patients with HCC‐CC were matched to patients with HCC and ICC on important clinical factors including tumor characteristics (size, vascular invasion, and differentiation) and underlying cirrhosis. Patients with HCC‐CC had rates of viral hepatitis comparable to patients with HCC (78.7% versus 80.0%), and 42.5% had underlying cirrhosis. When matched on tumor size, HCC‐CC was more poorly differentiated than HCC (68.3% versus 27.3%; P  < 0.001) and ICC (68.3% versus 34.8%; P  = 0.01) but had similar postresection survival (5‐year survival: HCC‐CC 49.7%, HCC 54.8%, ICC 68.7%; P  = 0.61) and recurrence (3‐year recurrence: HCC‐CC 57.9%, HCC 61.5%, and ICC 56%; P  = 0.58). Outcomes were similar between HCC‐CC and HCC when matched on underlying cirrhosis and tumor size. Cancer type was not predictive of survival or tumor recurrence. Survival after resection of HCC‐CC is similar to HCC when matched for tumor size, despite HCC‐CC tumors being more poorly differentiated. Exclusion of HCC‐CC from management strategies recommended for HCC, including consideration for liver transplantation, may not be warranted.